A simplified approach for the simultaneous qualification of bioanalytical methods for multiple species at late discovery stage. (May 2012) - Gordon, Justin; Johnson, Mike; Wu, Jing-Tao; Yu, Shaoxia
Background: Although not required to be GLP compliant, the bioanalytical methods intended to be used in supporting pharmacokinetic and exploratory toxicokinetic characterization of compounds in late drug-discovery stage are highly desirable to be qualified with respect to accuracy, precision, matrix effects and selectivity, as well as various stability assessments. Since the method qualification for each species is typically conducted separately, it is often resource-intensive and time-consuming.Results: In this work, we report a simplified approach to perform a non-GLP, multiple-species, bioanalytical-method qualification. In this approach, QC samples prepared from multiple species were quantified against standard curves from a single species. More importantly, multiple stability assessments were combined to produce combination stability QC samples under the assumption that if the combination stability QC samples met the acceptance criteria, so did each individual stability assessment.Conclusion: Using this simplified approach, a method qualification was typically completed in less than 2 weeks compared with the 5–8 weeks of a conventional method qualification. This approach was found to be useful for bioanalytical methods developed for both plasma and whole blood matrices